Genetic diagnostic yields of 354 Chinese ASD children with rare mutations by a pipeline of genomic tests - Zhang, Yue; Li, Ying; Guo, Ruolan; Xu, Wenjian; Liu, Xuanshi; Zhao, Chunlin; Guo, Qi; Xu, Wenshan; Ni, Xin; Hao, Chanjuan; Cui, Yonghua; Li, Wei (Frontiers in Genetics, 2023)
Purpose: To establish an effective genomic diagnosis pipeline for children with autism spectrum disorder (ASD) for its genetic etiology and intervention. Methods: A cohort of 354 ASD patients were obtained from Beijing Children's Hospital, Capital Medical University. Peripheral blood samples of the patients were collected for whole genome sequencing (WGS) and RNA sequencing (RNAseq). Sequencing data analyses were performed for mining the single nucleotide variation (SNV), copy number variation (CNV) and structural variation (SV). Sanger sequencing and quantitative PCR were used to verify the positive results. Results: Among 354 patients, 9 cases with pathogenic/likely pathogenic CNV and 10 cases with pathogenic/likely pathogenic SNVs were detected, with a total positive rate of 5.3%. Among these 9 CNV cases, 5 were de novo and 4 were inherited. Among the 10 de novo SNVs, 7 were previously unreported. The pathological de novo mutations accounts for 4.2% in our cohort. Conclusion: Rare mutations of CNVs and SNVs account for a relatively small proportion of ASD children, which can be easily detected by a genomic testing pipeline of combined WGS and RNAseq. This is important for early etiological diagnosis and precise management of ASD with rare mutations.